THE HEART: ITS STRUCTURE, FUNCTION, AND DISEASES - Maxmadaliyeva Aziza Lazizovna; Tursunmetov Ibodulla (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation:  This article provides general information about the structure and function of the heart, as well as the factors affecting its activity. It highlights the main types of heart diseases, their causes, and prevention methods. The article also includes useful lifestyle recommendations for maintaining a healthy heart and describes modern diagnostic techniques.